Hemiptera are Pests of Cotton (Texas Journal of Agriculture and Biological Sciences, 2022)
The article presents materials on the study of hemiptera pests of cotton, their species composition, harmful species, their food connections, biological characteristics, harmfulness, features of development phases, and measures to combat them are recommended.